Impact of chronic kidney disease on fetomaternal outcome: a case report - Khairnar, Neha; Bora, Ananya; Bava, Amarjeet Kaur (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Chronic kidney disease is a heterogenous group of disorders resulting from anatomical and physiological alterations in the kidney. Pregnancy might accelerate the renal disease-causing progression of renal failure, development of preeclampsia, anemia. This increases the risk of adverse fetomaternal outcomes including prematurity, fetal growth restriction, fetal deaths and development of hypertension, nephrotic syndrome, renal failure in the mother. Chronic kidney disease affects approximately 3% of pregnant women. This study was carried out to assess the course of chronic kidney disease in pregnancy and the effect it has on the fetal outcome. A case of chronic kidney disease presenting to the OBGY emergency unit was studied. a detail history was taken and examination was done. Baseline antenatal investigations were carried out. Special tests including renal Doppler, ophthalmoscopic examination, ECG, were done to assess the renal function. Treatment was started for control of hypertension and further progression of the disease. Pregnancy has adverse outcome when associated with acute kidney injury. Maternal hypertension and proteinuria are the major predisposing factors. Prematurity is one of the commonest fetal complications apart from growth restriction. Chronic kidney disease in pregnancy requires a multidisciplinary approach involving experienced obstetricians, nephrologists, radiologists, intensivists and neonatologists. The etiology, degree of renal dysfunction, development of additional obstetric complications determines the prognosis. Supportive therapy in the early course of the disease and timely definitive management as per the etiology is found to improve the feto-maternal outcome.